Semantics of Funtion Tables on the Reals - Hossain, Sameena (My University, 2013)
This thesis develops a formalism of function tables, inspired by the work of D. Parnas. It adapts that formalism so as to apply to topological partial algebras, involving continuous partial functions on the reals. In particular, it studies semantics-preserving transformations between two classes of tables: normal and inverted. This leads to a 3-valued logic different from that used by Wei Lei (2007) who investigated the application of function tables to "error algebras".
Keywords: Divergent values; Reals; Undefined; Function Tables